Efficacy and Safety of Chinese Medicine in Treating Arrhythmia: Meta-Analysis of Randomized Controlled Trials - Hanyu He (Hindawi Limited, 2021)
Objective. To evaluate the clinical efficacy of traditional Chinese medicine in the treatment of arrhythmia. Methods. The researchers searched CNKI, VIP, WF, PubMed, Web of Science, and Cochrane Library with the set-up themes as randomized controlled trials (RCTs) on the clinical efficacy of traditional Chinese medicine in the treatment of arrhythmia. This research evaluated all the retrieve literature and conducted selection based on the evaluation. Stata software was applied for meta-analysis. Results. 23 articles were retrieved with a total patient number of 2846. The results observed from the meta-analysis indicated the following: (1) compared with the result showed in placebo group, the traditional Chinese medicine group presented to have good efficacy, especially in the treatment of premature ventricular contractions. (2) In comparison with the western medicine group, the curative effect of Chinese medicine could approximately equal the therapeutic effect as western medicine. (3) Compared with the application of sole western medicine group, the combination of both traditional Chinese medicine and western medicine could have a better curative effect. Conclusion. In the treatment of arrhythmia disease, the application of traditional Chinese medicine can be considered as an effective method. In addition to that, the therapeutic effect obtained from the combination of both Chinese traditional medicine and western medicine is clinically better than that of the sole use of western medicine.